Pengaruh Beauty Vlogger, Iklan Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Scarlett Whitening Pada Masyarakat Di Kalimantan Timur - Fitriah Fitriah; Irma Yuliani; Tika Parlina (Borneo Islamic Finance and Economics Journal, 2023)
ABSTRACT Fitriah, 2023. "The Influence of Beauty Vloggers, Advertising, and Prices on the Decision to Purchase Scarlett Whitening Cosmetic Products in Communities in East Kalimantan". Thesis, Department of Islamic Economics, Faculty of Islamic Economics and Business, State Islamic University of Sultan Aji Muhammad Idris Samarinda. This research was supervised by Mrs. Irma Yuliani S.E, M.Sc as supervisor 1 and Mrs. Tika Parlina, M.M. as supervisor 2. The background of this research is that there was cosmetic product brands are increasingly developing with different variants and brands in each beauty company. Many beauty vlogger reviews explain the advantages and disadvantages of a product, the many advertisements that can attract consumers' attention through the models in the advertisement, and the prices that are already listed on a product to influence consumer purchasing decisions. This study aims to find the influence of beauty vloggers, advertising, and prices on purchasing decisions of Scarlett's cosmetic products from the perspective of Islamic economics in the people of East Kalimantan partially and simultaneously. The research method used in this study was a quantitative method to find the effect of the independent variables on the dependent variable. The sample in this study amounted to 96 respondents and the researchers rounded up to 100 respondents who were taken using the Cochran formula. Data analysis techniques in this study used data instrument tests (validity and reliability tests), classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, linearity test, autocorrelation test), multiple linear regression analysis, and hypothesis testing (t-test, test f, test the coefficient of determination). The results obtained from this study was that beauty vlogger has a positive and significant effect with a Tcount of 2.830 > Ttable 1.98498 with a significance of 0.006 <0.05, advertising has a positive and significant effect with a Tcount of 3.811 > Ttable 1.98498 with a significance of 0.000 <0.05, while the price has no effect with Tcount of 1.724 <Ttable 1.98498 with a significance of 0.088 > 0.05 on the decision to purchase scarlett whitening cosmetic products in people in East Kalimantan.